Discourse Analysis of the International University Ranking System: Lessons for the Iran Higher Education Curriculum - Mehdi Rajabloo; Badri Shahtalebi; Mohammad Hossein Yarmohamadian (Comparative Education Society of Iran ( CESIR), 2019)
The higher education system and its various dimensions are always subject to the influence of external discourses such as the "international ranking system of universities". Today, the curriculum as the core and reflector of the values, beliefs, and priorities of higher education policymakers is at the forefront of rational interaction with the ranking phenomenon of universities. In fact, the qualitative and quantitative evolution of the Iranian higher education system in the last four decades has led to a new phase that is not to be missed, as the slow but steady transition from the first generation to the fourth generation of universities in Iran has caused. Now that higher education policymakers are faced with the fundamental question of whether international university rankings can be considered as a transformational discourse for the curriculum. The present study, using discourse-based analysis, takes advantage of the forklift approach to analyze relevant texts and extract appropriate themes with three stages of description, interpretation and explanation. Research findings show that the phenomenon of international ranking of universities has the characteristics of a transformative discourse in the higher education system that affects all its dimensions. The paper suggests that Iran's higher education curriculum can adapt itself to the fourth generation of university challenges by combining traditional and modern discourse.